Loss and rebirth of the animal microtubule organizing center: how maternal expression of centrosomal proteins cooperates with the sperm centriole in zygotic centrosome reformation - Inoue, Daigo; Wittbrodt, Joachim; Gruss, Oliver (Bioessays, 2018)
Centrosomes are the main microtubule organizing centers in animal cells. In particular during embryogenesis, they ensure faithful spindle formation and proper cell divisions. As metazoan centrosomes are eliminated during oogenesis, they have to be reassembled upon fertilization. Most metazoans use the sperm centrioles as templates for new centrosome biogenesis while the egg's cytoplasm re-prepares all components for on-going centrosome duplication in rapidly dividing embryonic cells. We discuss our knowledge and the experimental challenges to analyze zygotic centrosome reformation, which requires genetic experiments to enable scrutinizing respective male and female contributions. Male and female knockout animals and mRNA injection to mimic maternal expression of centrosomal proteins could point a way to the systematic molecular dissection of the process. The most recent data suggest that timely expression of centrosome components in oocytes is the key to zygotic centrosome reformation that uses male sperm as coordinators for de novo centrosome production.